False-Positive Galactomannan Test Results in Multiple Myeloma - Shingen Nakamura; Yusaku Maeda; Ryohei Sumitani; Masahiro Oura; Kimiko Sogabe; Hikaru Yagi; Shiro Fujii; Takeshi Harada; Ken-ichi Matsuoka; Hirokazu Miki (Diseases)
Background/Objectives: Invasive pulmonary aspergillosis (IA) is a common infectious disease in patients with hematological diseases. The prevention, early detection, and establishment of treatment strategies for IA are important. The serum galactomannan antigen (GM) mycological test for IA diagnosis, included in the mycology criteria of the European Organization for Research and Treatment of Cancer-Invasive Fungal Infections Cooperative Group/National Institute of Allergy and Infectious Diseases Mycosis Study Group (EORTC/MSG), is widely used because of its high sensitivity and specificity. However, false-positive results are a concern. Methods: We retrospectively analyzed all GM tests performed at our department in the clinical practice setting between April 2003 and January 2012. Results: Of the 330 cases and 2155 samples analyzed, 540 (25%) were positive (≥0.5). Among the underlying diseases, positivity rates were the highest for multiple myeloma (MM), with 61.3%. By type, positivity rates for IgG, IgA, Bence-Jones protein, and IgD were 71.7%, 33.3%, 57.1%, and 34.6%, respectively. Seventeen out of eighteen cases that were GM-positive at MM diagnosis were false positives, according to the 2008 EORTC/MSG criteria. The IgG and GM values were not directly correlated. Of the seventeen false-positive cases identified, two developed IA during anti-myeloma treatments, and GM values did not become negative during the treatment in most cases. Conclusions: Although subclinical IA may be included in a higher GM index, the results may be prone to false positives; particularly in IgG-type MM, the results should thus be interpreted cautiously.